The Analysis of Flood Disaster Risk at Wonoasri Village, Tempurejo District, Jember Regency - Dianasari, Erni; Marchianti, Ancah Caesarina Novi; Prayitno, Hadi (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
A disaster is an event which causes an interference in a life and and livelihoods in a society. The flood disaster potential happened at Wonoasri village was caused by geographical location from Wonoasri village which is in the form of lowland and many formed lands that are concave. Thus almost each year, those places are experiencing flood. The flood is caused by the overflowing river at Sananrejo, Curahnongko and Mayang River which result in the occurrence of clogging due to sedimentation in some watersheds (referred as DAS in Indonesia). The aimed of this studied was to analyse the flood disaster risk at Wonoasri Village, Tempurejo Sub-District, Jember District.  To did that, this studied used quantitative method and descriptive-analysis.  The analysis of disaster risk was gained through weighing and disaster risk analysis matrix as well as interview and observations. Samples used in this present studied were 110 respondents. They were Wonoasri people consisting of Curahlele and Kraton area.  The leveled of flood disaster risk at Wonoasri Village, Tempurejo Sub-District, Jember District was in the yellow zone meaning that it was placed in the moderate risk leveled with a scale of 2 so the hypothesis statement of flood disaster risk leveled at Wonoasri Village, Tempurejo Sub-District, Jember District. To collected the data, this studied used questionnaire which measured the average score of overall respondents. Disaster risk could be overcome by decreasing the leveled of vulnerability and by increasing community capacity through educating them about disaster handling done through the socialization held periodically for the society and all organizations related to the disaster risk countermeasure. Keywords: Disaster risk analysis, Flood